A nanosheet-assembled porous rod-shaped BiVO4 triangular prism material and its preparation method

The preparation of nanosheets assembled porous rod-shaped BiVO4 triangular prism materials through one-step microwave radiation method has solved the problems of low surface area, complex process and high energy consumption of the existing BiVO4 preparation methods, and achieved an efficient, economical and environmentally friendly preparation process. The product has excellent photocatalytic performance and wide application prospects.

CN116143170BActive Publication Date: 2025-03-11XIJING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310002303.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-03
Publication Date
2025-03-11
Estimated Expiration
2043-01-03

AI Technical Summary

Technical Problem

The existing BiVO4 preparation methods have problems such as low surface area, complex process, high energy consumption, environmental pollution and high cost, and cannot meet the requirements of safety, simplicity, biocompatibility and economic benefits.

Method used

Using one-step microwave radiation method, nanosheets are quickly and uniformly prepared by microwave heating to assemble porous rod-shaped BiVO4 triangular prism material, avoiding the participation of acid and alkali and reaction conditions of high temperature and high pressure.

Benefits of technology

It has achieved a porous rod-shaped BiVO4 triangular prism material with low energy consumption, simple process operation and mild preparation conditions. It has high purity, good crystallinity and large specific surface area. It is suitable for photocatalysis, energy storage and conversion and pigment materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004034422150000011
    Figure HDA0004034422150000011
  • Figure HDA0004034422150000012
    Figure HDA0004034422150000012
  • Figure HDA0004034422150000021
    Figure HDA0004034422150000021
Patent Text Reader

Abstract

The invention discloses a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material and a preparation method thereof. Distilled water is used as a solvent to dissolve a mixed solution A of Bi(NO3)3·5H2O and CTAB and an ammonium metavanadate solution B respectively; the mixed solution A is added dropwise while the ammonium metavanadate solution B is vigorously stirred, and the stirring is continued to obtain a uniform reaction precursor mixed solution C; the precursor mixed solution C is transferred into a round-bottom flask and placed in a microwave reactor to be heated to 100° C. by microwave radiation to react; the resultant is cooled, centrifuged, washed and dried to obtain a porous rod-shaped BiVO4 triangular prism material assembled by nanosheets; the unique heating performance of microwave heating, which is fast and uniform and has no temperature gradient, is utilized to realize the synthesis of porous rod-shaped monoclinic BiVO4 triangular prisms without acid or alkali participation, simple operation, rapid controllability and environmental friendliness under the experimental parameters and operations selected by the invention; the obtained crystal product has high purity and good crystallinity and can be used in the field of photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The patent of this invention belongs to the field of bismuth vanadate material preparation, and specifically relates to a nanosheet assembled porous rod-shaped BiVO4 triangular prism material and a preparation method thereof. Background Art

[0002] Due to the massive use and scarcity of fossil fuels caused by the development of human society, energy shortage and environmental pollution are the two major problems facing the world today. Therefore, it is urgent to develop energy materials for sustainable development and solve environmental pollution problems. Photocatalytic technology is a green technology based on photocatalysts to achieve pollutant purification and solar energy conversion under the irradiation of light. Due to its own advantages such as no pollution, simple process, and direct use of solar energy, it provides a way to develop new energy materials and achieve environmental purification (Anandan S, Ashokkumar M. Sonochemical synthesis of Au-TiO2 nanoparticles for the sonophotocatalytic degradation of organic pollutants inaqueous environment [J]. Ultrasonics Sono-chemistry, 2009, 16 (3): 316-320). So far, most photocatalysts can only work in the ultraviolet light region, which only accounts for 4% to 5% of the total sunlight. Traditional photocatalytic materials, such as TiO2, have a wide band gap of about 3.2 eV, low quantum yield, poor solar energy utilization, and catalytic activity only in the ultraviolet region, which greatly limits their application (Kyung H, Lee J, Choi W. Simultaneous and synergistic conversion of dyes and heavy metal ions in aqueous TiO2 suspensions under visible-light illumination [J]. Environ. Sci. Technol, 2005, 39 (7): 2376-2382). Therefore, it is crucial to develop highly active catalysts that can respond to visible light to improve the utilization of solar energy by materials.

[0003] BiVO4 is a new type of non-titanium dioxide-based visible light photocatalytic material with a band gap of 2.2 to 2.4 eV. It has good application prospects due to its excellent chemical stability, non-toxicity and large light absorption range (Kudo A, Ueda K, Kato H, et al. Photocatalytic O2 evolution under visible light irradiation on BiVO4 in aqueous AgNO3 solution[J]. Catal. Lett, 1998, 53: 229-230). Among the three main crystal structures of BiVO4, monoclinic scheelite, tetragonal scheelite and tetragonal zircon, the distorted BiO8 dodecahedron in the crystal structure of monoclinic BiVO4 can generate an internal electric field with the VO4 tetrahedron, which is beneficial to the separation of photogenerated electron-hole pairs. Therefore, it has good photocatalytic activity and high light utilization rate (Zhao Z, Li Z, Zou Z. Electronic structure and optical properties of monoclinic clinobisvanite BiVO4[J]. Phys. Chem. Chem. Phys., 2011, 13(10): 4746-4753; Li H, Liu G, Duan X. Monoclinic BiVO4 with regular morphologies: hydrothermal synthesis, characterization and photocatalytic properties[J]. Mater. Chem. Phys, 2009, 115(1): 9-13), which has attracted the research of many scholars. Different preparation methods have different effects on the crystal phase and morphology of BiVO4, resulting in different photocatalytic properties.

[0004] At present, BiVO4 is mainly synthesized by hydrothermal method, sol-gel method, chemical precipitation method, solid phase method, combustion method and other methods (Chen Yuan, Liu Guocong, Yang Jiatian, et al. Hydrothermal synthesis of visible light responsive catalyst BiVO4 hexagonal microrods [J]. Journal of Inorganic Chemistry, 2011, 6(27): 1059-1064; Wang Min, Liu Qiong, Sun Yajie, et al. Preparation of Eu by sol-gel method 3+Doped BiVO4 and its visible light photocatalytic performance [J]. Journal of Inorganic Materials, 2013, 28(2): 153-159; Zhang Ping, Wang Huanying, Xu Baoen, et al. Preparation of BiVO4 by chemical precipitation method and its characterization [J]. Journal of Synthetic Crystals, 2008, 37(3): 716-781; Shamuga, Hou Xiaohu, Naren Tuya, et al. Preparation of nano-bismuth vanadate powder by combustion method and its properties [J]. Nonferrous Metals: Metallurgy, 2011(6): 45-49). However, most traditional BiVO4 preparation methods, including hydrothermal and solid-state methods, produce problems such as low-surface-area powders and coarse particles (Golmojdeh H, Zanjanchi M A. Characterization and photocatalytic activities of mesoporous silica containing BiVO4 or La-BiVO4 [J]. Chem. Eng. Technol., 2013, 36 (12): 2080-2086). In addition, the process often requires complex and strict preparation conditions, consumes a lot of time and energy, and requires the use of reagents such as acids or alkalis that are prone to cause environmental pollution, which cannot meet the requirements for safety, simplicity, biocompatibility and economic benefits. Summary of the invention

[0005] The present invention aims to provide a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material with low energy consumption, simple process operation and mild preparation reaction conditions and a preparation method thereof.

[0006] The present invention is implemented by the following scheme:

[0007] A method for preparing a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material comprises the following steps:

[0008] S1. According to the molar ratio of Bi:CTAB:V=2:2:3, 2.0615 g of analytically pure Bi(NO3)3·5H2O and 0.3872 g of analytically pure CTAB were dissolved in 115 mL of deionized water. After the solution was fully dissolved by magnetic stirring, it was placed in a microwave reactor and heated under reflux to obtain a uniform mixed solution A.

[0009] S2. According to the molar ratio of Bi:CTAB:V=2:2:3, 0.7457 g of analytically pure NH4VO3 accurately weighed was dissolved in 85 mL of deionized water and magnetically stirred to obtain a uniform ammonium metavanadate solution B;

[0010] S3, while vigorously stirring the ammonium metavanadate solution B, add the mixed solution A prepared in step S1 dropwise, and continue stirring evenly after the addition is completed to obtain a uniform reaction precursor solution C;

[0011] S4. The reaction precursor solution C in step S3 is transferred into a 500 mL three-necked flask and placed in a microwave reactor, and the reaction is carried out at a heating temperature of 100° C. for 90 min-150 min. After the reaction is completed and naturally cooled, the precipitate is obtained by centrifugation and filtration, and the precipitate is washed with distilled water and ethanol for multiple times and then dried to obtain a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material.

[0012] Furthermore, the solution in step S1 was mixed on a magnetic stirrer at a rotation speed of 800 rpm for 15 min until fully dissolved, and heated under reflux at 100° C. for 60 min in a microwave reactor to obtain a uniform mixed solution A.

[0013] Furthermore, in step S2, the mixture is fully mixed on a magnetic stirrer at a rotation speed of 800 rpm for 15 minutes to obtain a uniform ammonium metavanadate solution B.

[0014] Furthermore, in step S3, the mixed solution A prepared in step S1 is added dropwise, and stirring is continued until 10 minutes after the mixed solution is added dropwise, to obtain a uniform reaction precursor solution C.

[0015] Furthermore, in step S4, the obtained product is centrifuged at a speed of 5000 rpm for 2 minutes, the precipitate is filtered to obtain, washed with distilled water for 8 to 10 times, washed with ethanol for 1 to 2 times, and then dried in an oven at 70° C. for 24 hours to obtain a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material.

[0016] A nanosheet-assembled porous rod-shaped BiVO4 triangular prism material has a product morphology of a porous rod-shaped BiVO4 triangular prism with a length of 4.62 to 14.72 μm, a width of 1.94 to 4.01 μm and a thickness of 0.19 to 1.40 μm, which is composed of nanosheets with a particle size of 0.36 to 1.41 μm and a thickness of 49 to 184 nm.

[0017] Furthermore, the space group of the product is I2 / a, and the unit cell parameters and

[0018] α=γ=90.0° and β=90.38°, the strongest peak corresponds to the crystal plane index (121), and the lattice spacing is 0.309nm.

[0019] The present invention aims at the problems that the existing BiVO4 preparation process usually uses acid and alkali to control the phase and morphology, resulting in complex and unstable processes, high energy consumption caused by high temperature and high pressure reaction conditions, high cost and environmental unfriendliness caused by many types of raw materials, and the product cannot be obtained by one-step reaction and needs post-processing, and proposes a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material and a preparation method thereof. The method of the present invention does not require acid and alkali to participate in the regulation, the process is safe and simple, the energy consumption is low, the cost is high, and it is stable and controllable. It can achieve the regulation of the morphology and phase of the BiVO4 product by a one-step microwave radiation method; the obtained product is a porous rod-shaped monoclinic BiVO4 triangular prism assembled by nanosheets, the sample has high purity, good crystallinity and high specific surface area, and has broad application prospects and important research significance in the fields of photocatalysis, energy storage and conversion, pigment materials, etc.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] (1) The present invention adopts a one-step microwave radiation technology, utilizing the unique heating properties of microwaves, which are fast, uniform, and without temperature gradient. The preparation process does not require high temperature and high pressure treatment, and does not require subsequent treatment. The reaction is carried out under normal pressure system, and the equipment requirements are low.

[0022] (2) The method of the present invention can achieve the regulation of the morphology and phase of the pure monoclinic BiVO4 material without the participation of acid or alkali, which solves the problems of complex process, poor stability and high raw material composition caused by pH adjustment with acid or alkali in conventional methods.

[0023] (3) The method of the present invention does not require high temperature and high pressure reaction conditions, the process equipment is simple, the reaction process is fast and controllable, the raw materials are cheap and easily available and environmentally friendly, the operation is simple, the conditions are mild, the energy consumption is low, the cycle is short, the repeatability is good, and the efficiency is controllable, which meets the requirements of the preparation process of monoclinic BiVO4, such as safety, simplicity, eco-friendliness and high economic benefits.

[0024] (4) This method uses analytically pure Bi(NO3)3·5H2O, NH4VO3 and cetyltrimethylammonium bromide (CTAB). Through multiple explorations and precise control of core experimental parameters and operating methods such as the molar ratio of raw materials, temperature, and time, it is possible to quickly and controllably prepare porous rod-shaped monoclinic BiVO4 triangular prism materials assembled by nanosheets under mild conditions of normal pressure and low temperature without the participation and regulation of acid or alkali. The prepared monoclinic BiVO4 product has high purity, good crystallinity, and large specific surface area.

[0025] The microwave used in the present invention is a short-wavelength electromagnetic wave with high energy and strong penetration ability. The reaction system is heated by microwaves to achieve a rapid reaction at a relatively low temperature. In the early stage of the reaction, highly active reactant particles collide with each other under the action of the microwave field to form small crystals of monoclinic bismuth vanadate, and then under the action of a surfactant, the small crystals self-assemble under the induction of a template agent according to the principle of minimum energy, and finally form a porous rod-like monoclinic bismuth vanadate structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the X-ray diffraction (XRD) pattern of the monoclinic BiVO4 sample when the reaction time is 90 min;

[0027] Figure 2 This is the crystal structure diagram of sample 14-0688 phase monoclinic BiVO4;

[0028] Figure 3 This is a 7k-fold scanning electron microscope (SEM) image of the monoclinic BiVO4 sample when the reaction time is 90 min;

[0029] Figure 4 This is a 50k-fold scanning electron microscope (SEM) image of the monoclinic BiVO4 sample when the reaction time is 90 min;

[0030] Figure 5 Schematic diagram of the synthesis morphology of monoclinic BiVO4 sample;

[0031] Figure 6 is the X-ray diffraction (XRD) pattern of the monoclinic BiVO4 sample when the reaction time is 150 min;

[0032] Figure 7 This is a 7k-fold scanning electron microscope (SEM) image of the monoclinic BiVO4 sample when the reaction time is 150 min;

[0033] Figure 8 This is a 13k-fold scanning electron microscope (SEM) image of the monoclinic BiVO4 sample when the reaction time is 150 min. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0035] Example 1 Preparation of BiVO4 Sample 1 Using Microwave Radiation Technology

[0036] Prepare reaction precursor solution C: According to the molar ratio of Bi:CTAB:V=2:2:3, accurately weigh 2.0615g analytical pure Bi(NO3)3·5H2O and 0.3872g analytical pure CTAB and dissolve them in 115mL deionized water. Mix the solution on a magnetic stirrer at 800rpm for 15min until fully dissolved and transfer it to a round-bottom flask. The flask is placed in a "Midea PJ21C-AU" with a power of 1000W and a frequency of 2450MHz. The reaction system is at normal pressure and equipped with a reflux device. In a microwave reactor, heat and reflux at 100°C for 60 minutes to obtain a uniform mixed solution A; accurately weigh 0.7457g of analytical pure NH4VO3 is dissolved in 85mL of deionized water, and fully mixed on a magnetic stirrer at a speed of 800rpm for 15 minutes to obtain a uniform ammonium metavanadate solution B; while vigorously stirring the ammonium metavanadate solution B, add the mixed solution A dropwise, and continue stirring until 10 minutes after the addition of the mixed solution A is completed, to obtain a uniform reaction precursor solution C and transfer it to a 500mL three-necked flask.

[0037] Microwave reaction: The three-necked flask containing the reaction precursor solution C was placed in a "Midea PJ21C-AU" microwave reactor with a power of 1000 W, a frequency of 2450 MHz, a reaction system of normal pressure and a reflux device, and reacted at a heating temperature of 100° C. for 90 minutes.

[0038] Centrifugation and washing: After the reaction is completed and cooled naturally, the product is centrifuged at 5000 rpm for 2 minutes, filtered to obtain the precipitate, washed with distilled water for 8 to 10 times, washed with ethanol 1 to 2 times, and dried in an oven at 70°C for 24 hours to obtain porous rod-shaped BiVO4 triangular prisms assembled by nanosheets.

[0039] Characterization: X-ray diffraction results show that the product is a pure phase of monoclinic BiVO4. The X-ray diffraction (XRD) pattern of the product when the reaction time is 90 min is as follows: Figure 1 As shown, the angles at 2θ=18.988°, 28.586°, 28.822°, 28.947°, 30.548°, 34.494°, 42.464°, 46.711°, 47.305° and 53.243° all correspond to the characteristic peaks of monoclinic BiVO4 of standard JCPDS card No. 14-0688, respectively, with (011), (121), (040), (200), (051), (240), (042) and The corresponding crystal planes have intensities of 25.0, 30.0, 100.0, 95.0, 25.0, 12.0, 12.0, 16.0, 16.0 and 18.0 au, respectively; the space group of the product is I2 / a, and the unit cell parameters are and

[0040] α=γ=90.0° and β=90.38°, the strongest peak corresponds to the crystal plane index (121), and its crystal structure is as follows Figure 2 As shown, the lattice spacing is 0.309nm.

[0041] Scanning electron microscope SEM image ( Figure 3 , 4 ) shows that the morphology of the product is composed of nanosheets with a particle size of 0.98 to 3.53 μm and a thickness of 18 to 85 nm, and microrods with a length of 4.31 to 15.23 μm, a width of 1.80 to 5.71 μm, and a thickness of 0.38 to 0.98 μm. The schematic diagram of the morphology is shown in Figure 5 shown.

[0042] Example 2 Preparation of BiVO4 Sample 2 Using Microwave Radiation Technology

[0043] Prepare reaction precursor solution C: According to the molar ratio of Bi:CTAB:V=2:2:3, accurately weigh 2.0615g analytical pure Bi(NO3)3·5H2O and 0.3872g analytical pure CTAB and dissolve them in 115mL deionized water. Mix the solution on a magnetic stirrer at 800rpm for 15min until fully dissolved and transfer it to a round-bottom flask. The flask is placed in a "Midea PJ21C-AU" with a power of 1000W and a frequency of 2450MHz. The reaction system is at normal pressure and equipped with a reflux device. In a microwave reactor, heat and reflux at 100°C for 60 minutes to obtain a uniform mixed solution A; accurately weigh 0.7457g of analytical pure NH4VO3 is dissolved in 85mL of deionized water, and fully mixed on a magnetic stirrer at a speed of 800rpm for 15 minutes to obtain a uniform ammonium metavanadate solution B; while vigorously stirring the ammonium metavanadate solution B, add the mixed solution A dropwise, and continue stirring until 10 minutes after the addition of the mixed solution A is completed, to obtain a uniform reaction precursor solution C and transfer it to a 500mL three-necked flask.

[0044] Microwave reaction: The three-necked flask containing the reaction precursor solution C was placed in a "Midea PJ21C-AU" microwave reactor with a power of 1000 W, a frequency of 2450 MHz, a reaction system of normal pressure and a reflux device, and reacted at a heating temperature of 100° C. for 150 min.

[0045] Centrifugation and washing: After the reaction is completed and cooled naturally, the product is centrifuged at 5000 rpm for 2 minutes, filtered to obtain the precipitate, washed with distilled water for 8 to 10 times, washed with ethanol 1 to 2 times, and dried in an oven at 70°C for 24 hours to obtain porous rod-shaped BiVO4 triangular prisms assembled by nanosheets.

[0046] Characterization: X-ray diffraction results show that the product is a pure phase of monoclinic BiVO4. The X-ray diffraction (XRD) pattern of the product when the reaction time is 150 min is as follows: Figure 6 As shown, the angles at 2θ=18.669°, 28.586°, 28.822°, 28.947°, 30.548°, 35.221°, 40.040°, 46.711°, 53.243° and 53.310° all correspond to the characteristic peaks of monoclinic BiVO4 of standard JCPDS card No. 14-0688, respectively. (121), (040), (002), (240), and (161) crystal plane, with intensities of 25.0, 30.0, 100.0, 95.0, 25.0, 14.0, 10.0, 16.0, 18.0 and 18.0 au, respectively; the space group of the product is I2 / a, and the unit cell parameters are and α=γ=90.0° and β=90.38°, the strongest peak corresponds to the crystal plane index (121), and its crystal structure is as follows Figure 2 As shown, the lattice spacing is 0.309nm.

[0047] Scanning electron microscope SEM image ( Figure 7 , 8 ) shows that the morphology of the product is composed of nanosheets with a particle size of 0.36 to 1.41 μm and a thickness of 49 to 184 nm, and microrods with a length of 4.62 to 14.72 μm, a width of 1.94 to 4.01 μm, and a thickness of 0.19 to 1.40 μm. The schematic diagram of the morphology is shown in Figure 5 shown.

[0048] Comparative Example 1 of Example 1:

[0049] (Zhang L, Chen D, Jiao X. Monoclinic structured BiVO4 nanosheets: hydrothermal preparation, formation mechanism, and coloristic and photocatalytic properties [J]. J. Phys. Chem. B, 2006, 110 (6): 2668-2673), Zhang et al. synthesized the target product by hydrothermal method as follows: 5.0 mmol (2.45 g) of Bi(NO3)3·5H2O was dissolved in 10.0 mL of 4.0 mol·dm -3 5.0 mmol (0.58 g) of NH4VO3 was added to 10.0 mL of 2.0 mol·dm -3 Then, 0.72 mmol (0.25 g) of SDBS was added to the above two solutions, and after stirring for 0.5 hours, the two solutions were mixed to obtain a reaction precursor solution; then, 2.0 mol·dm -3 The pH value of the reaction precursor solution is adjusted to 7.0 with a NaOH solution and stirred for 0.5 h; the precursor solution is poured into a stainless steel autoclave lined with polytetrafluoroethylene until 80% of the volume of the autoclave is occupied, and the autoclave is heated at 200°C for 1.5 hours under autogenous pressure; after the autoclave is cooled to room temperature, a bright yellow precipitate is separated by filtration, washed several times with distilled water and anhydrous ethanol, and then dried at 100°C for 4 hours to obtain the target product; the product obtained by this method is monoclinic BiVO4, the reaction is carried out under high temperature and high pressure conditions, the energy consumption is large, and the reaction process requires the use of acid and alkali for pH conditions, which increases the complexity of the process operation, and the obtained product is a BiVO4 nanosheet with a thickness of 10 to 40 nm.

[0050] There is an essential difference between the patent of the present invention and the comparative example; the patent of the present invention has distinct innovation.

[0051] Comparative Example 2 of Example 1:

[0052] (Eda S, Fujishima M, Tada H. Low temperature-synthesis of BiVO4 nanorods using polyethylene glycol as a soft template and the visible-light-activity for copper acetylacetonate decomposition [J]. Appl. Catal., B, 2012, 125: 288-293), Eda et al. prepared the target product by using polyethylene glycol as a soft template through the template method as follows: 15 mmol Bi(NO3)3·5H2O, 15 mmol NH4VO3 and 20 mL of polyethylene glycol (PEG-200) with a molecular weight of 200 were dissolved in 25 mL of 2M HNO3 solution and stirred magnetically for 2 h; 20 mL of the mixed solution was added 1.5M NaOH, then heated at 370K for 2h, the obtained solid was washed with distilled water, and then dried in a vacuum dryer at room temperature; subsequently, the particles were calcined in air at a temperature range of 673 to 973K to obtain a monoclinic BiVO4 product with a nanorod structure composed of nanoparticles with an average particle size of 31.3nm; this method requires a large number of raw materials and reagents, the operation needs to be carried out step by step, and the reaction temperature is high, and it is impossible to achieve a low-cost, environmentally friendly, efficient and simple preparation process.

[0053] There is an essential difference between the patent of the present invention and the comparative example; the patent of the present invention has distinct innovation.

[0054] Comparative Example 3 of Example 1:

[0055] In (Zhang X, Ai Z, Jia F, et al. Selective synthesis and visible-lightphotocatalytic activities of BiVO4 with different crystalline phases [J]. Mater. Chem. Phys., 2007, 103 (1): 162-167), Zhang et al. synthesized monoclinic and tetragonal BiVO4 powders by a hydrothermal process as follows: an aqueous solution of Bi(NO3)3·5H2O and a stock solution of NH4VO3 were mixed at a Bi:V molar ratio of 1:1; the mixture was stirred in air at room temperature for 0.5 h, or poured into a 25 mL polytetrafluoroethylene-lined stainless steel autoclave until 80% of the volume of the autoclave was filled; the autoclave was heated at 160, 180 or 200 ° C under autogenous pressure for 2 4h, then air-cooled to room temperature; the resulting precipitate was collected, washed with deionized water and anhydrous ethanol three times, and then dried in a 50°C atmospheric oven for several hours to obtain bismuth vanadate materials with different morphologies and phases: tetragonal BiVO4 composed of irregular particles was obtained by reaction at room temperature, and the particles were agglomerated; dendrites were found in the samples synthesized under hydrothermal conditions, and the samples synthesized at 140°C were a mixture of tetragonal and monoclinic BiVO4 with a branch size of about 200nm; the samples synthesized at 180 or 200°C were pure monoclinic phases, and the branches and trunks of the dendrites in the samples synthesized at 200°C were about 500nm and 10μm, respectively. The tetragonal phase products obtained by this preparation method at low temperatures do not have the application prospects of photocatalysis, while monoclinic or mixed phase products require higher reaction temperatures and have a long process cycle.

[0056] There is an essential difference between the patent of the present invention and the comparative example; the patent of the present invention has distinct innovation.

[0057] Example 3 Preparation of BiVO4 Sample 3 Using Microwave Radiation Technology

[0058] Prepare reaction precursor solution C: According to the molar ratio of Bi:CTAB:V=2:2:3, accurately weigh 2.0615g analytical pure Bi(NO3)3·5H2O and 0.3872g analytical pure CTAB and dissolve them in 115mL deionized water. Mix the solution on a magnetic stirrer at 800rpm for 15min until fully dissolved and transfer it to a round-bottom flask. The flask is placed in a "Midea PJ21C-AU" with a power of 1000W and a frequency of 2450MHz. The reaction system is at normal pressure and equipped with a reflux device. In a microwave reactor, heat and reflux at 100°C for 60 minutes to obtain a uniform mixed solution A; accurately weigh 0.7457g of analytical pure NH4VO3 is dissolved in 85mL of deionized water, and fully mixed on a magnetic stirrer at a speed of 800rpm for 15 minutes to obtain a uniform ammonium metavanadate solution B; while vigorously stirring the ammonium metavanadate solution B, add the mixed solution A dropwise, and continue stirring until 10 minutes after the addition of the mixed solution A is completed, to obtain a uniform reaction precursor solution C and transfer it to a 500mL three-necked flask.

[0059] Microwave reaction: The three-necked flask containing the reaction precursor solution C was placed in a "Midea PJ21C-AU" microwave reactor with a power of 1000 W, a frequency of 2450 MHz, a reaction system of normal pressure and a reflux device, and reacted at a heating temperature of 100° C. for 120 min.

[0060] Centrifugation and washing: After the reaction is completed and cooled naturally, the product is centrifuged at 5000 rpm for 2 minutes, filtered to obtain the precipitate, washed with distilled water for 8 to 10 times, washed with ethanol 1 to 2 times, and dried in an oven at 70°C for 24 hours to obtain porous rod-shaped BiVO4 triangular prisms assembled by nanosheets.

Claims

1. A method for preparing a porous rod-shaped BiVO4 triangular prism material assembled from nanosheets, characterized in that The following steps are involved: S1. According to the molar ratio of Bi: CTAB: V = 2: 2: 3, weigh 2.0615 g of analytically pure Bi(NO3)3·5H2O and 0.3872 g of analytically pure CTAB and dissolve them in 115 mL of deionized water. After the solution is fully dissolved by magnetic stirring, it is placed in a microwave reactor and heated under reflux to obtain a uniform mixed solution A. S2. According to the molar ratio of Bi: CTAB: V = 2: 2: 3, 0.7457 g of analytically pure NH4VO3 was dissolved in 85 mL of deionized water by magnetic stirring to obtain a uniform ammonium metavanadate solution B. S3, while vigorously stirring the ammonium metavanadate solution B, adding the mixed solution A prepared in step S1 dropwise, and then continuing to stir evenly after the addition is completed, to obtain a uniform reaction precursor solution C; S4, the reaction precursor solution C in step S3 was transferred into a 500 mL three-necked flask and placed in a microwave reactor, and the reaction was carried out at a heating temperature of 100 ° C for 90 min-150 min; after the reaction was completed and naturally cooled, the precipitate was centrifuged and filtered to obtain a precipitate, which was washed with distilled water and ethanol for multiple times and then dried to obtain a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material; The solution in step S1 is mixed on a magnetic stirrer at a speed of 800 rpm for 15 min until fully dissolved, and heated under reflux at 100° C. for 60 min in a microwave reactor to obtain a uniform mixed solution A; In step S4, the obtained product is centrifuged at a speed of 5000 rpm for 2 min, and the precipitate is filtered to obtain the precipitate, which is washed with distilled water for 8 to 10 times, and then washed with ethanol for 1 to 2 times, and then dried in an oven at 70° C. for 24 h to obtain a nanosheet-assembled porous rod-shaped BiVO4 triangular prism material.

2. The method for preparing the nanosheet-assembled porous rod-shaped BiVO4 triangular prism material according to claim 1, characterized in that: In the step S2, the mixture is fully mixed on a magnetic stirrer at a rotation speed of 800 rpm for 15 min to obtain a uniform ammonium metavanadate solution B.

3. The method for preparing the nanosheet-assembled porous rod-shaped BiVO4 triangular prism material according to claim 1, characterized in that: In the step S3, the mixed solution A prepared in the step S1 is added dropwise, and stirring is continued until 10 minutes after the mixed solution is added dropwise, to obtain a uniform reaction precursor solution C.

4. A nanosheet-assembled porous rod-shaped BiVO4 triangular prism material prepared according to the preparation method according to any one of claims 1 to 3, characterized in that: The morphology of the product is porous rod-shaped BiVO4 triangular prisms with a length of 4.62~14.72 μm, a width of 1.94~4.01 μm, and a thickness of 0.19~1.40 μm, which are composed of nanosheets with a particle size of 0.36~1.41 μm and a thickness of 49~184 nm.

5. The nanosheet-assembled porous rod-shaped BiVO4 triangular prism material according to claim 4, characterized in that: The space group of the product is I2 / a, unit cell parameters a=5.195 Å, b=11.701 Å and c=5.092 Å, α=γ=90.0° and β=90.38°, the strongest peak corresponds to the crystal plane index (1 - 21), and the lattice spacing is 0.309 nm.

Citation Information

Patent Citations

  • Manganese molybdate material having micron rod structure and assembled by nano sheets

    CN102502846A

  • Preparation method of microwave-synthesized monoclinic system olivary pucherite BiVO4

    CN103224251A